Cognitive dysfunction in arterial hypertension patients - M. M. Petrova; N. A. Shnayder; O. V. Eremina (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study the severity of cognitive dysfunction (CD) in patients with arterial hypertension (AH).Material and methods. The study included 147 patients: 97 (66%) women and 50 (34%) men with AH of various stages. Patients age varied from 40 to 75 years (mean age 63,2+10,8 years). The participants were selected by stratified randomization method, according to inclusion and exclusion criteria. Various neuro-psychological tests were used in the study.Results. In AH patients, CD prevalence and severity were positively associated with AH stage. Compared to controls, AH individuals were significantly different in terms of neuro-psychological test results, including changes in voluntary activity regulation, cognitive process neurodynamics, and dynamic disturbances of memory and space functions.Conclusion. The study results provided new insights on CD prevalence and clinical manifestation in AH patients.